Development and validation of new RP-HPLC method for the determination of amlodipine in pharmaceutical wastewater using SPE for extraction - Helal Uddin, A.B.M.; Alaama, Mohammed; Kamarbashrudin, Siti Khadijah Rose; Izat, I'zma (2016)
The presence of pharmaceuticals in the environment had become a cause for snowballing concern in recent years. A wide range of pharmaceuticals had been discovered in fresh and marine waters and it had recently been shown that even in small quantities these compounds have the potential to cause detriment to aquatic life. Being ranked as number one in the Top 50 Drugs by Expenditures in the Malaysian Statistics on Medicine, amlodipine might also contribute to the emerging issue of pharmaceutical wastewater pollution. This research project is designed to develop a methodology in detecting amlodipine analysis in pharmaceutical wastewater. Cetrizine was used as internal standard and samples were analysed using Agilent 1200 Series RP- HPLC equipped with quaternary pump and auto injector. Samples were injected to C18 column and the mobile phase consisted of ammonium acetate buffer (pH=4 adjusted using glacial acetic acid) and acetonitrile in the ratio 60- 40. The flow rate was 1 ml/min and UV detector was used for the detection and the wavelength was 248nm. Solid phase extraction (SPE) is used in this study for the extraction of amlodipine and IS. The recovery of amlodipine was evaluated over three QC concentrations and the recovery was in the range of 65%-72%. The method was linear over the range of 30-5000 ng/ml of amlodipine in wastewater. In general, the method can be used for the analysis of amlodipine in wastewater.